Community dynamics towards the existence of toll roads in Indonesia: a literature and spatial study - Rahmadana, Muhammad Fitri; Putra, Ilham Mirzaya (Frontiers in Built Environment, 2025)
Infrastructure is the backbone of the development of a region. However, infrastructure must also be designed with sustainability in mind including toll road construction. This study investigates the societal dynamics and impacts of toll roads in Indonesia from 2019 to 2023. Through a literature review of 92 relevant articles obtained from scientific journals, books, and reports using keywords “toll” and “community,” trends and perceptions regarding toll roads were analyzed. The evaluative descriptive method, guided by Neuman was employed to assess the trends rationally. Findings reveal a declining growth rate (−5.43%) in articles related to tolls and society, averaging 18 scientific articles per year. Economic and social aspects were most discussed, followed by legal and environmental considerations. Regionally, toll roads' impacts varied: positive economic effects were noted in urban and toll gate adjacent areas, while negative impacts were observed in rural regions reliant on passing vehicle trade and agriculture. Socially, industrial zones, dense population centers, and potential tourism spots benefited, but issues like land scarcity and social disparities widened. Environmental risks included damage to sensitive ecosystems, water sources, air quality, and agricultural land, particularly in disaster-prone regions. The study emphasizes the need for comprehensive planning and mitigation strategies to address toll roads' multifaceted impacts on society, economy, and the environment. By understanding these dynamics, policymakers and planners can develop sustainable infrastructure solutions that benefit all stakeholders. This research contributes valuable insights to transportation infrastructure development and management in Indonesia, aiding policymakers and urban planners in making informed decisions.